2020
DOI: 10.1042/bsr20193308
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis and clinical implications of immune cell infiltration in gastric cancer

Abstract: The immune infiltration of patients with gastric cancer (GC) is closely associated with clinical prognosis. However, previous studies failed to explain the different subsets of immune cells involved in immune responses and diverse functions. The present study aimed to uncover the differences in immunophenotypes in a tumor microenvironment (TME) between adjacent and tumor tissues and to explore their therapeutic targets. In our study, the relative proportion of immune cells in 229 GC tumor samples and 22 paired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…The presence of tumor-infiltrating immune cells (TIICs) in the tumor microenvironment is usually associated with poor prognosis ( Fridman et al, 2012 ) and has been characterized recently in GC ( Li et al, 2019 ; Wang et al, 2020 ; Wei et al, 2020 ; Wu et al, 2020 ). To determine if the non-canonical Wnt signatures are correlated with immune cell infiltration, the correlation between the two gene signatures and markers of specific immune cell types was assessed using GEPIA (“signature-to-signature” comparison).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of tumor-infiltrating immune cells (TIICs) in the tumor microenvironment is usually associated with poor prognosis ( Fridman et al, 2012 ) and has been characterized recently in GC ( Li et al, 2019 ; Wang et al, 2020 ; Wei et al, 2020 ; Wu et al, 2020 ). To determine if the non-canonical Wnt signatures are correlated with immune cell infiltration, the correlation between the two gene signatures and markers of specific immune cell types was assessed using GEPIA (“signature-to-signature” comparison).…”
Section: Resultsmentioning
confidence: 99%
“…Cumulative evidence indicates that immune cell infiltration can affect the progression and prognosis of GC [ 33 , 34 ]. We evaluated the correlation between LAMA4 expression and immune cell infiltration in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in this study, a series of bioinformatics analyses indicated that MCEMP1 might be an indicator of the status of the TME in GC patients. Furthermore, many studies have demonstrated that the TME is signi cantly correlated with the initiation, progression and metastasis of GC [14,15] and that TICs are closely related to the clinical prognosis of GC patients [16].…”
Section: Discussionmentioning
confidence: 99%